(untitled) (Journal of Economic Research & Business Administration, 2021)
For successfully solving the problem of entering Kazakhstan among the 30 developed countries of the world, a decisive transition to an innovative economy and the adoption of measures to modernize the labor market are required. Under “modernization of the labor market” it is proposed to understand the modernization in accordance with the latest scientific achievements, new requirements and norms in this area, adopted in the leading developed countries. The purpose of the article is to select the option of modernizing the labor market in Kazakhstan based on the analysis of labor market models of the leading developed countries of the world. The main directions of scientific research are determining the relationship between the models of socio-economic development of countries and their labor markets, identifying the features of labor market models, identifying of factors affecting the efficiency of the labor market and, accordingly, on the position of countries in the world according to the global competitiveness index (GCI). Scientific and practical significance of the work: different interpretation of the concept of “modernization of the labor market” is given, which led to comparative analysis of models of labor markets in developed countries and Kazakhstan. The methods of grouping, correlation and regression analysis were applied. The study of the relationship between GDP, employment, average wages and labor productivity allowed to characterize the features of the functioning of labor markets. The research results made it possible to concretize and systematize measures to modernize the labor market. The labor market modernization project should become an integral part of the program of economic reforms in the country. Key words: labor market models, developed countries, Kazakhstan, the impact of the labor market on the country’s competitiveness.